AB0825 IMPACT OF AROMATASE INHIBITOR TREATMENT ON BONE MINERAL DENSITY AND PREVALENT VERTEBRAL FRACTURE. (June 2019) - Daldoul, Cyrine; Amri, Nejla El; Laataoui, Sadok; Baccouch, Khadija; Belaid, Imtinen; Zeglaoui, Hela; Bouajina, Elyes
Abstract : Background: In recent years, despite the growing incidence of breast cancer, a reduction in mortality has been observed. Adjuvant therapy with aromatase inhibitors (AI) has contributed to a longer disease free survival. However these molecules induce a hyper bone remodeling, modifying the bone architecture and thus increasing the fracture risk. The new guidelines indicate extension of treatment duration up to 10 years. So special precautions must be established in order to avoid bone mineral density (BMD) decrease and to reduce fracture risk. Objectives: The aim of this study was to evaluate the impact of AI treatment on BMD and to screen vertebral fracture (VF) in post menopausal women with breast cancer. Methods: A clinical cross sectional study was carried between August 2018 and December 2018, including post-menopausal women with non-metastatic breast cancer. Each woman had an extensive medical history and physical examination. BMD was measured using dual energy X absorptiometry DeXa at femoral neck, total hip and at lumbar spine. We used the WHO criteria for the diagnosis of osteoporosis and osteopenia. Vertebral fractures were screened by performing a vertebral fracture (VFA) image. VF grade 1 were excluded. Results: Thirty-six post-menopausal women were examined in our rheumatology department. The mean age was 59.5±10.38 years with an average body mass index (BMI) of 30.7 kg/m 2 [15.81-38.28].The average age of menopause was 45.5±5.25 years.The mean length of menopause was 14 years [2.1-31]. The mean duration of breast cancer follow-up was 71.7 months. 22 patients underwent chemotherapy and radiotherapy.Mean femoral neck BMD was 0.805 g/cm 3 [0.647-1.049 g/cm 3 ] and the vertebral BMD was 1.003 g/cm 3 [0.739-1.314g/cm 3 ].According to the WHO classification, 12 women (34.6%) had osteoporosis, 15 (42.3%) had osteopenia and 9 (19.2%) had normal BMD. 9 patients showed signs of osteoporosis at femoral neck and 8 had osteoporosis at lumbar spine. 10 subjects (27.8%) had VF identified by VFA, which were grade 2 and 3 in respectively 8 and 2 vertebra. No multiple VF were assessed. No statistically significant difference was found between women with and without VF for age, BMD value, and duration of follow-up or previous fragility fracture. We did not find a significant correlation between treatment length and BMD at either site: femoral neck (p=0.42), total hip (p=0.783) and lumbar spine (p=0.357). Conclusion: This data has shown that approximately one-third of patients receiving AI treatment have at least one vertebral fracture, and 40% had osteoporosis. Therefore we need to screen bone mineral density and fracture in women under AI therapy. Disclosure of Interests: None declared